Concentration‐dependent effects of dutasteride on prostate‐specific membrane antigen (PSMA) expression and uptake of 177Lu‐PSMA‐617 in LNCaP cells. Issue 12 (24th June 2019) - Kranzbühler, Benedikt; Salemi, Souzan; Umbricht, Christoph A.; Deberle, Luisa M.; Müller, Cristina; Burger, Irene A.; Hermanns, Thomas; Sulser, Tullio; Eberli, Daniel
Abstract: Background: Prostate‐specific membrane antigen (PSMA)‐based imaging and therapy are increasingly used in the management of prostate cancer. However, low PSMA surface expression in certain patients is a limitation for PSMA‐based technologies. We have previously shown that high doses of dutasteride, a 5α‐reductase inhibitor generally used for the treatment of benign prostatic enlargement, increase the PSMA expression in vitro. We now further analyzed the concentration‐ and time‐dependent effects of dutasteride in LNCaP cells. Methods: Androgen receptor (AR) expressing prostate cancer cells (LNCaP) were treated for 7 to 14 days with vehicle control (0.1% dimethyl sulfoxide) or different concentrations of dutasteride (0.25 , 0.5 , 1 , and 5 μM). In addition to cell proliferation, PSMA surface expression was assessed using flow cytometry (FACS) and immunocytochemistry. Total PSMA and AR expression was analyzed by capillary western immunoassay (WES). In addition, tumor cell uptake and internalization assays of 177 Lu‐PSMA‐617 were performed. Results: Dutasteride treatment resulted in a significant upregulation of PSMA surface expression compared to vehicle control after 7 days in all tested concentrations. After 14 days a further, concentration‐dependent increase of PSMA surface expression was detectable. Total PSMA protein expression significantly increased after treatment of cells with high concentrations of dutasteride using 5 μM for 7 or 14 days. However, when lower concentrations were used total PSMA expression was not significantly altered compared to vehicle control. Further testing revealed a dose‐dependent increase in uptake and internalization of 177Lu ‐PSMA‐617 after 7 and 14 days. Though, a significantly increased uptake was only observed using a 5 μM dutasteride concentration for 7 days as well as 1 and 5 μM for 14 days. Conclusion: Our investigations revealed a concentration‐ and time‐dependent effect of dutasteride on PSMA expression and uptake of 177Lu ‐PSMA‐617 in LNCaP cells. A short‐term treatment of patients with high doses of dutasteride might increase the detection rate of PSMA‐based imaging and increase the effect of 177Lu ‐PSMA‐617 therapy via upregulation of PSMA expression.